Optimizing the expediency of TNFi in rheumatoid arthritis: offering a TNFi holiday in patients having reached low-disease activity in the maintenance phase. (December 2014) - van Ingen, Iris LA; Lamers-Karnebeek, Femke; Jansen, Tim L
Abstract : Introduction: The treatment of rheumatoid arthritis (RA) has been revolutionized since the introduction of biological disease-modifying antirheumatic drugs such as tumour necrosis factor alpha inhibitors (TNFi), and clinical remission has become a realistic target in the treatment strategy. Discontinuation strategies of TNFi therapy after reaching sustained remission or low-disease activity (LDA) have been emerging. These strategies are important considering the risk–benefit profile of TNFi, as well as looking at them from a cost-economic point of view. Areas covered: This article presents an overview of recent major studies on TNFi withdrawal, and tapering and about the safety of doing so. Expert opinion: Although data are still limited, tapering or discontinuing TNFi in some RA patients may well be possible, especially in the early RA patients who are methotrexate naive. Also, a substantial group of longer established RA patients can stop or taper TNFi, particularly when ultrasonography signals are negative. However, before making the decision of implementing it in the routine care for RA patients, more predictors for successful discontinuation are desired.